Penetrasi Sosial dalam Mencari Pasangan Pada Aplikasi Kencan Online Bumble - Ita Puspitasari; Monika Pretty Aprilia (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The Bumble application is an online dating-based partner search application that is currently popular. The bumble application is an application that brings together the opposite sex by viewing information on profiles such as hobbies, interests, and preferences. This application is believed to be able to provide a solution to the speed of meeting a suitable partner. The purpose of this study was to determine the process of forming interpersonal relationships towards more intimate communication. This researcher focuses on female users of the Bumble application as the holder of control in forming a relationship. The theory used to support this research is social penetration proposed by Irwin Altman and Dalmas. This research was investigated using a descriptive qualitative method with a constructivism study. Data collection techniques used in this study were observations and interviews with five female informants who used the Bumble application. Based on the results of the research that through the activities of Bumble users who interact with each other, it can be found the application of social penetration theory. Starting from the four stages of the social penetration process, namely the orientation stage, affective exploration, affective exchange and stable exchange, female users of the Bumble application apply penetration theory as a process of forming a new relationship with an unknown person.